DIFFERENCES IN SHOOTING ACCURACY AND EFFICIENCY OF THE TOP WOMEN'S TEAMS AT THE 2021 TOKYO OLYMPIC GAMES - Sanja Bajgorić; Muris Đug; Rađević Nenad (Sport Scientific And Practical Aspects, 2025)
This study is established on the aim to analyse a game and determine differences in a shot efficacy in an offence the woman’s handball national teams at the Olympic games in Tokyo 2021. Four national teams were analysed: France, Russia, Norway and Sweden. To analyse a game in the offence, 12 variables were used: total number of shots (sut_uk), efficient number of shots (sut_usp), total number of shots from 6 meters (sut_m6_uk), efficient number of shots from 6 meters (sut_m6_us), total number of shots from wings (sut_kril_uk), the efficient number of shots from wings (sut_kr_us), total number of shots from 9 meters (sut_m9_uk), efficient number of shots from 9 meters (sut_m9_us), total number of shots from 7 meters (sut_m7_uk), efficient number of shots from 7 meters (sut_m7_us), total number of fast centres (brzc_uk) and total number of efficient fast centres (sut_brzc_us). All national teams had the approximal number of efficient shots on a goal. The highest number of efficient shots from 6 m had the French and Norwegian national teams. From the wing position, the highest number of efficient shots had the Norwegian national team, while the lowest number of efficient goals from the wing position had the Russian national team. The Norwegian and French national teams were approximately efficient in the shot’s realisation from 9 m. In a realisation of the fast centre, the Russian national team stands out with the highest number and the French national team had the lowest number of efficient shots.